Wishin' and hopin' : a Christmas story - Lamb, Wally (New York : Harper, 2009)
"Set in the fictional town of Three Rivers, Connecticut, the story of fifth grader Felix Funicello in the months leading up to Christmas 1964"--Provided by publisher
Keywords: Connecticut -- Fiction